Whole-genome sequencing for identification of the source in hospital-acquired Legionnaires' disease. Issue 4 (August 2017) - Rosendahl Madsen, A.M.; Holm, A.; Jensen, T.G.; Knudsen, E.; Lundgaard, H.; Skov, M.N.; Uldum, S.A.; Kemp, M.
Summary: Acquisition of Legionnaires' disease is a serious complication of hospitalization. Rapid determination of whether or not the infection is caused by strains of Legionella pneumophila in the hospital environment is crucial to avoid further cases. This study investigated the use of whole-genome sequencing to identify the source of infection in hospital-acquired Legionnaires' disease. Phylogenetic analyses showed close relatedness between one patient isolate and a strain found in hospital water, confirming suspicion of nosocomial infection. It was found that whole-genome sequencing can be a useful tool in the investigation of hospital-acquired Legionnaires' disease.